The Effectiveness of Affective Commitment Training to Increase Work Engagement in Sales Employees: a Systematic Literature Review Study - Nainggolan, Christyne Anggrica Avfrilia Boru; Retno Suminar, Dewi; Hadi, Cholichul (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Work engagement was recognized as a key factor in improving performance, innovation, and organizational success amid the complexities of global dynamics. Global data showed low engagement levels, with only 23% of employees feeling engaged in their work. Affective commitment, as the emotional attachment of employees to their organization, emerged as a primary predictor of sustained engagement. This study aimed to systematically examine the role of affective commitment in enhancing work engagement and to explore its mediating relationship with organizational factors such as leadership style and work climate. Using a Systematic Literature Review (SLR) approach, the study analyzed 30 articles from Scopus, Web of Science, and Google Scholar, following the PRISMA protocol. The findings revealed that affective commitment served as a direct predictor, a mediator in the relationship between ethical and servant leadership with engagement, and a buffer against stress and turnover. Furthermore, organizational factors such as high-involvement work practices and an ethical climate were found to reinforce affective commitment. The study’s practical implications emphasized the importance of value-based human resource development strategies, the strengthening of ethical leadership culture, and the creation of a supportive work environment to foster sustainable engagement and improve organizational competitiveness in the modern era. Keterlibatan kerja sebagai faktor kunci dalam meningkatkan kinerja, inovasi, dan keberhasilan organisasi di tengah dinamika global yang kompleks. Data global menunjukkan rendahnya tingkat keterlibatan, di mana hanya 23% karyawan merasa engaged dalam pekerjaan mereka. Affective commitment, sebagai keterikatan emosional karyawan terhadap organisasi, muncul sebagai prediktor utama keterlibatan kerja yang berkelanjutan. Penelitian ini bertujuan untuk mengkaji secara sistematis peran affective commitment dalam meningkatkan work engagement, serta mengeksplorasi hubungan mediatif dengan faktor-faktor organisasi seperti gaya kepemimpinan dan iklim kerja. Metode penelitian menggunakan pendekatan Systematic Literature Review (SLR) terhadap 30 artikel dari database Scopus, Web of Science, dan Google Scholar, dengan proses seleksi mengikuti protokol PRISMA. Hasil analisis menunjukkan bahwa affective commitment berperan sebagai prediktor langsung, mediator hubungan kepemimpinan etis dan servant leadership dengan engagement, serta sebagai pelindung terhadap stres dan turnover.. Implikasi praktis penelitian ini menekankan perlunya strategi pengembangan sumber daya manusia berbasis nilai, penguatan budaya kepemimpinan etis, dan penciptaan lingkungan kerja yang suportif untuk membangun keterlibatan kerja yang berkelanjutan dan meningkatkan daya saing organisasi di era modern.